Closure of the fascial defect during laparoscopic umbilical hernia repair: a randomized clinical trial. Issue 3 (23rd January 2020) - Christoffersen, M. W.; Westen, M.; Rosenberg, J.; Helgstrand, F.; Bisgaard, T.
Abstract : Background: The objective of the study was to analyse patient‐reported outcome measures (PROMs), seroma formation, long‐term recurrence and chronic pain after closure of the fascial defect in patients undergoing laparoscopic umbilical hernia mesh repair. Methods: This was a randomized double‐blinded trial in patients undergoing elective laparoscopic umbilical hernia repair comparing sutured closure of the fascial defect before intraperitoneal onlay mesh (IPOM) repair with a no‐closure IPOM repair. Postoperative pain, movement limitations, discomfort and fatigue were registered before surgery and on postoperative days 1–3, 7 and 30. Seroma formation, quality of life and cosmesis were assessed at day 30, and at 2 years of follow‐up. Recurrence (clinical and reoperation) and chronic pain were assessed after 2 years. Results: Eighty patients were randomized. Median defect sizes in closure and no‐closure groups were 2·5 (range 1·5–4·0) and 2·5 (2·0–5·5) cm respectively ( P = 0·895). There were no significant differences in early and late postoperative pain or in any other early or late PROMs, except for early fatigue which was higher in the closure group ( P = 0·011). Seroma formation after 30 days was significantly reduced after closure (14 of 40; 35 (95 per cent c.i. 22 to 51) per cent) compared with no closure (22 of 38; 58 (42 to 72) per cent) ( P = 0·043). Cumulative recurrence after 2 years was lower in the closure group: 5 of 36 (7 (3 to 17) per cent) versus 12 of 37 (19 (10 to 33) per cent) for no closure ( P = 0·047). Conclusion: Closure of the fascial defect in laparoscopic umbilical hernia IPOM repair significantly reduced early seroma formation and long‐term recurrence without inducing side‐effects such as pain, or other early or late PROMs. Registration number: NCT01962480 ( https://www.clinicaltrials.gov ). Abstract : This RCT of patients undergoing elective laparoscopic umbilical hernia repair compared sutured closure of the fascial defect before intraperitoneal onlay mesh (IPOM) repair with a non‐closure IPOM repair.